1997
DOI: 10.1159/000023823
|View full text |Cite
|
Sign up to set email alerts
|

What Have Mast Cells To Do with Edema Formation, the Consecutive Repair and Fibrinolysis?

Abstract: Mast cells (MC) have been implicated in the activation of vascular endothelial cells, capillary leak formation, transmigration of white blood cells, and translocation of fibrinogen (and other plasma molecules) into the tissues, with consecutive edema formation. However, the mechanisms of repair that lead to tissue reconstitution after MC activation and edema formation have not been defined so far. In the present article, the possible contribution of MC to repair, in particular fibrinolysis, is discussed. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…The same mediators released during an allergic response are found in wounded tissues. Histamine, proteases, TNF and PGs are known to induce vasodilation and increase vascular permeability [68]. Endothelial cells release IL-3 and thrombin, which enhance migration, proliferation and local differentiation of mast cells [69].…”
Section: Mast Cell Stabilisation and Wound Healingmentioning
confidence: 99%
“…The same mediators released during an allergic response are found in wounded tissues. Histamine, proteases, TNF and PGs are known to induce vasodilation and increase vascular permeability [68]. Endothelial cells release IL-3 and thrombin, which enhance migration, proliferation and local differentiation of mast cells [69].…”
Section: Mast Cell Stabilisation and Wound Healingmentioning
confidence: 99%
“…It has been shown in several studies that the number of mast cells increases in venous thrombosis, whereby in deep venous thrombosis mast cells accumulate in vicinity to the vasa vasorum at the site of the thrombus [3]. In auricular thrombosis mast cells are found in the upper endocardium.…”
Section: Mast Cells and Thrombosismentioning
confidence: 99%
“…In auricular thrombosis mast cells are found in the upper endocardium. Mast cell accumulation has also been described in liver vein thrombosis and pulmonary embolism [3][4][5]. It has also been shown that mast cell deficient mice have an increased risk to develop fatal thrombosis [6].…”
Section: Mast Cells and Thrombosismentioning
confidence: 99%
“…Dear Sir, In their interesting paper, Valent et al [1] suggest that mast cells might have functions beyond those involved in allergic and inflammatory reactions. Mast cells are the source of both tPA and heparin and are able to include fibrinolysis in vitro.…”
mentioning
confidence: 99%
“…In these patients, the generation of a clot inside a critically obstructed coronary artery would be prolonged and delayed because of the late appearance of thrombin. Combined with endogenous thrombolysis linked to mast cell activation [1], this mechanism could protect against sudden cardiac death, the event consistently associated with occlusive coronary thrombi.…”
mentioning
confidence: 99%